Essentials of Plastic Surgery - Jones, Alex P. (Thieme Medical Publishers, Incorporated, 2022)
A must-have companion resource to test knowledge of plastic surgery essentials Essentials of Plastic Surgery: Q&A Companion, Second Editionby renowned plastic surgeons Alex P. Jones and Jeffrey E. Janis mirrors expanded content and new chapters in the parent book,Essentials of Plastic Surgery, Third Edition. The third edition of the parent book includes 127 chapters, which reflects the increased scope, breadth, and depth of plastic surgery since publication.